2011
DOI: 10.1111/j.1745-4557.2011.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Shelf Life Stability of Cakes

Abstract: The effects of new ingredient strategies to slow down starch retrogradation rate in cakes were investigated. In this study, devil's fudge cakes were formulated using gum, modified starch and enzyme technology. Cake samples that were prepared with combinations of gums, bacterial amylases and pregelatinized starch were found to have slower starch retrogradation rates. An accelerated shelf life protocol was followed to observe the effect of predescribed ingredients on slowing the starch retrogradation rate. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…2B. The positive effect of pregelatinized starches on cakes texture has been proved (Hesso et al, 2014;Sozer et al, 2011), while this is the first attempt to investigate their effect on the protein structure. In this study, pregelatinized wheat starch (PWS) was tested in batter model systems.…”
Section: Mean Frequencies (Cmmentioning
confidence: 94%
See 1 more Smart Citation
“…2B. The positive effect of pregelatinized starches on cakes texture has been proved (Hesso et al, 2014;Sozer et al, 2011), while this is the first attempt to investigate their effect on the protein structure. In this study, pregelatinized wheat starch (PWS) was tested in batter model systems.…”
Section: Mean Frequencies (Cmmentioning
confidence: 94%
“…Finally, recently it was demonstrated that adding pregelatinized starch improves cake softness and softness retaining during storage (Hesso, Loisel, Chevallier, & Le-Bail, 2014;Sozer, Bruins, Dietzel, Franke, & Kokin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The dextrins are thought to hinder gluten-starch interactions and interrupt the starch network (Goesaert, Leman, Bijttebier, & Delcour, 2009;Goesaert, Slade, Levine, & Delcour, 2009). Hydrocolloids enhance water retention and limit its redistribution within starchy baked food structures (Sozer, Bruins, Dietzel, Franke, & Kokini, 2011), which provides an anti-staling effect. The type, source and molecular weight of hydrocolloids are all important factors that influence the anti-staling ability in different food products (Guarda, Rosell, Benedito, & Galotto, 2004;Gujral, Haros, & Rosell, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cakes and breads are the products that have the highest consumption rate among baked goods (SOZER et al, 2011a). Cake quality is affected by the ingredients used in an appropriate and properly balanced formulation, and mixing and baking procedures (TIREKI, 2008).…”
Section: Introductionmentioning
confidence: 99%